Venom peptide analysis of Vipera ammodytes meridionalis (Viperinae) and Bothrops jararacussu (Crotalinae) demonstrates subfamily-specificity of the peptidome in the family Viperidae - Munawar, Aisha; Trusch, Maria; Georgieva, Dessislava; Spencer, Patrick; Frochaux, Violette; Harder, Soenke; Arni, Raghuvir K. [UNESP]; Duhalov, Deyan; Genov, Nicolay; Schlueter, Hartmut; Betzel, Christian (Royal Soc Chemistry, 2011)
Snake venom peptidomes are valuable sources of pharmacologically active compounds. We analyzed the peptidic fractions (peptides with molecular masses < 10 000 Da) of venoms of Vipera ammodytes meridionalis (Viperinae), the most toxic snake in Europe, and Bothrops jararacussu (Crotalinae), an extremely poisonous snake of South America. Liquid chromatography/mass spectrometry (LC/MS), direct infusion electrospray mass spectrometry (ESI-MS) and matrix-assisted desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) were applied to characterize the peptides of both snake venoms. 32 bradykinin-potentiating peptides (BPPs) were identified in the Crotalinae venom and their sequences determined. 3 metalloproteinase inhibitors, 10 BPPs and a Kunitz-type inhibitor were observed in the Viperinae venom peptidome. Variability in the C-terminus of homologous BPPs was observed, which can influence the pharmacological effects. The data obtained so far show a subfamily specificity of the venom peptidome in the Viperidae family: BPPs are the major peptide component of the Crotalinae venom peptidome lacking Kunitz-type inhibitors (with one exception) while the Viperinae venom, in addition to BPPs, can contain peptides of the bovine pancreatic trypsin inhibitor family. We found indications for a post-translational phosphorylation of serine residues in Bothrops jararacussu venom BPP (<(S)under bar>QGLPPGPPIP), which could be a regulatory mechanism in their interactions with ACE, and might influence the hypotensive effect. Homology between venom BPPs from Viperidae snakes and venom natriuretic peptide precursors from Elapidae snakes suggests a structural similarity between the respective peptides from the peptidomes of both snake families. The results demonstrate that the venoms of both snakes are rich sources of peptides influencing important physiological systems such as blood pressure regulation and hemostasis. The data can be used for pharmacological and medical applications.